Screening and assessment of polyneuropathy in adult patients and the effect of folic acid administration on the course of neuropathy - Pawar, Namrata; Bhosale, Uma (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Multiple nerves damage (polyneuropathy) characterized by symmetrical sensory symptoms, such as numbness, paraesthesia, pain, andweakness predominantly in distal parts and pathophysiology depends on the underlying disease. Folic acid, (vitamin B9) deficiency causes many neurodegenerative and cerebrovascular diseases. Supplementation enhances neurodevelopment and provides neuroprotection in someneurological diseases by growth, differentiation and regeneration of the CNS. Methods: Prospective open-label study included 60 patients visiting at tertiary care hospital of either sex with an age range between 18 to 70 years. We evaluated the role of folic acid in the course of neuropathy in all enrolled patients using various neuropathy scores like diabetic neuropathy symptom questionnaire, survey of autonomic symptoms questionnaire, neuropathy deficit (or disability) score, standardized nerve conduction studies and cardiac autonomic reflex test. Results: NCV in the diabetic and alcoholic patients was statistically significant in almost all motor and sensory nerves in both upper and lower limb. In epileptic patients, was more significant in the lower limb in both motor and sensory nerves. In nutritional deficient patients was significant in only 2 nerves. In the diabetic patient, we also observed significance in DNS questionnaire (0.017). Conclusions: Since folate is effective, cheap, treatment and, devoid of apparent toxicity for this obscure, chronic, neurological disorders would be agent justified. A significant improvement in the results was seen majorly in diabetic group, thus can be included for them.